A novel experimental approach for nanostructure analysis: simultaneous small‐angle X‐ray and neutron scattering. Issue 3 (13th May 2020) - Metwalli, Ezzeldin; Götz, Klaus; Lages, Sebastian; Bär, Christian; Zech, Tobias; Noll, Dennis M.; Schuldes, Isabel; Schindler, Torben; Prihoda, Annemarie; Lang, Herbert; Grasser, Jürgen; Jacques, Mark; et al.
Abstract : A portable small‐angle X‐ray scattering instrument with geometrical dimensions suitable for installation at the D22 instrument was designed and constructed for simultaneous small‐angle X‐ray and neutron scattering experiments at ILL. Abstract : Exploiting small‐angle X‐ray and neutron scattering (SAXS/SANS) on the same sample volume at the same time provides complementary nanoscale structural information in two different contrast situations. Unlike an independent experimental approach, the truly combined SAXS/SANS experimental approach ensures the exactness of the probed samples, particularly for in situ studies. Here, an advanced portable SAXS system that is dimensionally suitable for installation in the D22 zone of ILL is introduced. The SAXS apparatus is based on a Rigaku switchable copper/molybdenum microfocus rotating‐anode X‐ray generator and a DECTRIS detector with a changeable sample‐to‐detector distance of up to 1.6 m in a vacuum chamber. A case study is presented to demonstrate the uniqueness of the newly established method. Temporal structural rearrangements of both the organic stabilizing agent and organically capped gold colloidal particles during gold nanoparticle growth are simultaneously probed, enabling the immediate acquisition of correlated structural information. The new nano‐analytical method will open the way for real‐time investigations of a wide range of innovative nanomaterials and will enable comprehensive in situ studies on biological systems. The potential development of a fully automated SAXS/SANS system with a common control environment and additional sample environments, permitting a continual and efficient operation of the system by ILL users, is also introduced.